Work-life balance and job stress in the administrative staff of the National University of the Altiplano Puno in 2024 - Melitón, López Paz, Peregrino; Antonio, López Cueva, Milton; Porfirio, Enríquez Salas,; Antonieta, López Cueva, Lourdes (Edelweiss Applied Science and Technology, 2025)
Administrative staff are essential as they organize and help managing activities in organizations. In universities, their function is to support academic activities through administrative management. In Perú, the administrative staff of public universities are called public workers and enter the administrative career to work in Peruvian State entities; and is part of the Peruvian civil service. The objective of this research is to analyze the relationship between work-life balance and job stress of the administrative staff of the National University of the Altiplano Puno in 2024. In the methodology, the quantitative approach, non-experimental design and correlational transectional type were used. The sample was made up of 180 administrative workers. The instruments used were the documentary analysis and the self-administered questionnaire with closed questions with a Likert scale. Finally, the proposed hypothesis was accepted because the results demonstrated the existence of a weak positive correlation between work-life balance. Furthermore, it was concluded that 90% of administrative staff perceived levels of job stress in the intervals: occasionally and often.